Single molecule mass photometry of nucleic acids - Li, Y; Struwe, WB; Kukura, P (Oxford University Press, 2020)
Mass photometry is a recently developed methodology capable of measuring the mass of individual proteins under solution conditions. Here, we show that this approach is equally applicable to nucleic acids, enabling their facile, rapid and accurate detection and quantification using sub-picomoles of sample. The ability to count individual molecules directly measures relative concentrations in complex mixtures without need for separation. Using a dsDNA ladder, we find a linear relationship between the number of bases per molecule and the associated imaging contrast for up to 1200 bp, enabling us to quantify dsDNA length with up to 2 bp accuracy. These results introduce mass photometry as an accurate, rapid and label-free single molecule method complementary to existing DNA characterization techniques.